2002
DOI: 10.1159/000047193
|View full text |Cite
|
Sign up to set email alerts
|

A Low Serum sICAM-1 Level May Assist in the Exclusion of Neonatal Infection

Abstract: Serum levels of soluble intercellular adhesion molecule-1 (sICAM-1) in 46 samples from 46 infants undergoing intensive care were studied. Residual serum remaining after routine electrolyte analysis was utilised. sICAM-1 levels were determined by ELISA. Blind retrospective chart review was employed to determine whether infants were infected. Serum levels were significantly elevated in infants with proven and probable infection, compared with non-infected infants (p < 0.001). sICAM-1 levels in serum were compara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…sICAM-1 rose in the peripheral blood of both asphyxiated and infected neonates on the 3rd and 5th postnatal days. Several investigators have found increased sICAM-1 serum levels in septicemic newborns (23,24,(34)(35)(36). To the authors' knowledge, measurements of sICAM-1 in neonatal peripheral blood following perinatal asphyxia have not been reported.…”
Section: Discussionmentioning
confidence: 81%
“…sICAM-1 rose in the peripheral blood of both asphyxiated and infected neonates on the 3rd and 5th postnatal days. Several investigators have found increased sICAM-1 serum levels in septicemic newborns (23,24,(34)(35)(36). To the authors' knowledge, measurements of sICAM-1 in neonatal peripheral blood following perinatal asphyxia have not been reported.…”
Section: Discussionmentioning
confidence: 81%
“…Circulating levels of soluble ICAM-1 (sICAM-1) have been associated with mortality in ICU patients [ 32 , 33 ], adult systemic inflammatory response syndrome (SIRS) and sepsis severity [ 33 – 35 ], and bacteremia [ 36 ]. However among neonates, this association is less consistent with some studies reporting no association between sICAM-1 and sepsis [ 37 , 38 ], while others demonstrate a positive association [ 39 – 42 ], even in the early stages of sepsis [ 43 ]. Soluble-VCAM-1 (sVCAM-1) has been shown in some adult studies to be associated with sepsis [ 32 , 34 ], whereas in neonates circulating sVCAM-1 was not associated with sepsis but rather only with bacteremia [ 43 ].…”
Section: Introductionmentioning
confidence: 85%
“…Our data suggest that the best initial cutoff would be 274 mg/L, with no false-negatives and a very low rate of false-positives. Edgar and colleagues 24 studied 46 newborns and reported that a low level of serum sICAM-1 might help exclude infection. Our results support this suggestion because the negative predictive value of 100% that we obtained means that all the newborns with sICAM-1 concentrations below 274 mg/L will not be affected by HC ĂŸ sepsis.…”
Section: Discussionmentioning
confidence: 99%